Analysis Of Determining Flavonoid Contents In Red Onion (Allium Cepa L.) Extract Using Multiple Methods - Arzak, La Ode Miftahul; Pratama, Mamat (Pharmaceutical Reports, 2025)
Shallots contain secondary metabolites such as flavonoids, kaempferol, flavonglycosides and quercetin. This research aims to conduct a literature study on the analysis of the levels of flavonoid compounds in shallots (Allium cepa L). This research uses a literature study where references are obtained through the Google Scholar and Elsevier websites, then articles are selected that match the criteria in the literature study. Based on the search carried out, 7 correct articles were obtained. From the results of the literature study, it can be concluded that the assay methods that can be used to determine the flavonoid content of shallots are High Performance Liquid Chromatography (HPLC) and UV-Vis Spectrophotometer. And there are also several flavonoid derivative compounds contained in shallots from published articles, such as quercetin and anthocyanin.